(untitled) (Eurasian Journal of Research, Development and Innovation, 2022)
The principal objective of this paper was to explore what rhetorical strategies and stylistic devices of President Barack Obama use in his political speeches and how these devices help him to gain the audience’s attention and render the message. The speeches of President B. Obama were analyzed in order to highlight the patterns of the usage of rhetorical strategies and to investigate the stylistic devices which are aimed at making speech more emphatic, expressive and persuasive. The method chosen for the study was content analysis including generalization and evaluation of the results. The results of the research showed a significant contribution of stylistic means to persuade the listeners on an emotional level or even to manipulate them.